(untitled) (EAAE Joint Publishings, 2026)
Built environment education (BEE) presents an interdisciplinary field of education intended for children and young people. Besides fields of architecture, urban design, art, landscape architecture, etc., it includes different social aspects such as community engagement, culture, and heritage, thus being important not only for future architects but for every citizen. On the other hand, in Education for Sustainable Development (ESD), the main topics of interest are key sustainability issues such as climate change, lack of biodiversity, sustainable consumption, etc. Likewise, promoting critical thinking and decision-making in a collaborative way, ESD coincides with methods in architecture such as participatory design. This research focuses on developing a BEE co-design method with integrated ESD components that can be applied as a learning tool. To answer the main research question of how we can successfully design vertical gardens (VGs) in schools that act as BEE tools for tackling sustainability issues, study first presents a set of educational gamified workshops aiming at the development of co- design method that includes topics of environmental, ecological, and social VG benefits, and second, its evaluation results. The workshops’ input was specially developed for the ages of 12, 13, and 14 and later conducted through the collaboration of architects, a pedagogue, teachers, and students in one primary school in Belgrade, Serbia, in April 2023. This study is part of the author’s doctoral research, whose related objective is the design of a toolkit for a gamified educational co-design method for VGs that can later be applicable to other schools. Therefore, this paper concludes the tested design process evaluation, suggesting recommendations for its improvement. Finally, this research contributes to filling the previously identified gap in the scientific literature on VGs’ educational benefits and the urgent need for education on nature-based solutions in Serbia.